Content analysis and readership surveys of Garfield and Jane comic strips - Aguila, Almond Pilar N.
This study is not just a general content analysis and readership survey of both Garfield and Jane comic strips but rather an analysis of their violence and sexual contents. Since most readers of comic strips are children, there should be an effort to look into sensitive topics such as these. The respondents were readers ages 9-14 from two exclusive schools (Miriam Grade School and Claret Grade School). There were 75 males and 75 females in the group. Children involved in the survey had a positive attitude toward the comic strips. All were Garfield comic strips readers, but only 35 were Jane comic strip readers. The survey showed that children were aware of the degrees of sex and violence in comics yet they continue to read them. For the content analysis, degrees for sexual and violent contents in comic strips were made, that is, minimal, moderate and excessive. Observations on the texts and visuals were made on 30 comic strips. Garfield comic strips portrayed violent behavior through the dialogue and the illustrations while Jane comic strips had their sexual contents mostly in the visuals.